Variations in nutrient intake of dairy cows and feed balance in urban and peri-urban dairy production systems in Ethiopia - Mekasha, Yoseph; Tegegne, Azage; Yami, A.; Umunna, N.N. (Ethiopian Society of Animal Production, 2003)
An on-farm monitoring study was carried out in the urban and peri-urban dairy production systems in the Addis Ababa milk shed to assess variations in on farm nutrient intake of dairy cows (Holstein Friesian X Zebu) and feed balance. Ninety seven cows, with parities above two and at the beginning of lactation, representing three production sub systems (intra-urban, large peri-urban and secondary town) were considered for the study. Mean basal and supplement (P<0.001) and total (P<0.01) DM intake, mean CP intake (P<0.001) from basal, supplement and total diet, and mean energy intake from basal (P<0.001) and supplement (P<0.01) varied among the production subsystems. Basal and supplemental dry matter, crude protein and energy intakes varied (P<0.001) among herd size groups (i.e. small, medium and large), where medium sized farms had higher (P<0.001) supplemental dry matter, crude protein and energy intakes, while small farms had higher (P<0.001) basal dry matter, crude protein and energy intakes. Basal and total (P<0.001) crude protein intakes were greatest in the long rainy season. Annual dry matter and crude protein intakes close to calculated requirements for intra-urban and secondary town, but 1.5% lower than requirement for large peri-urban farms. Annual energy intake, however, was 36.3% lower than the requirement for the entire production sub-systems. Thus, the level of feeding management should be improved in order to exploit the genetic potential of crossbred dairy cows in intensively managed urban and peri-urban dairy system.